Loyalitas Dan Kepuasan Konsumen Terhadap Kualitas Produk Suatu Merek Barang - Tirta Mulyadi; Pandu Adi Cakranegara; Srifatmawati Ahmad; Muhammad Azizi; Kelemens Mere (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The quality of an item able to have a positive impact on increased the selling value of an item or product. The product will be sold if consumers are satisfied with the goods purchased so that they are more loyal in spended their money to get the desired item. The purpose of this study was to determine the effect on product quality of an item and the brand of an item on consumer satisfaction and consumer loyalty. The method used in this research is a qualitative method in the form of a literature study in the field of marketing management of a product. The method of wroted scientific articles is by used qualitative methods and literature studies or Library Research. The product quality of an item affects consumer satisfaction, the brand image of an item affects consumer satisfaction, the brand image of an item affects consumer satisfaction, the quality of an item affects consumer loyalty, the brand of an item affects consumer loyalty, and consumer satisfaction affects consumer loyalty. Keywords : Consumer Satisfaction, Consumer Loyalty, Product Quality, Product Brand Image.